Letter to the Editor on the article, 'Perioperative Complications Associated with Routine Preoperative Glucocorticoid Use Among Patients Undergoing Pituitary Surgery with Normal Preoperative HPA Axis: A Retrospective Cohort Study': by Magnaye and Paz-Pacheco, published in JAFES Vol 40. No. 1 - Fatimah, Eisha; Usman, Sarosh; Muhammad Aqib Farooq Khan (Journal of the ASEAN Federation of Endocrine Societies, 2026)
This letter addresses the recent study by Magnaye et al., which investigated the impact of routine preoperative glucocorticoid administration in patients with a normal hypothalamic-pituitary-adrenal (HPA) axis undergoing pituitary surgery. The authors are commended for their valuable contribution to understanding steroid-related perioperative outcomes. However, we highlight the need for further clarification regarding the wide range of steroid regimens reported and the absence of detailed information on timing, indications, and factors influencing steroid administration. Additionally, differentiating between transient and permanent postoperative diabetes insipidus could provide deeper insight into the observed higher incidence among steroid-treated patients. Addressing these aspects, along with establishing standardized steroid protocols, could enhance the specificity and clinical applicability of the study’s findings.